Tick-borne agents in domesticated and stray cats from the city of Campo Grande, state of Mato Grosso do Sul, midwestern Brazil - André, Marcos Rogério [UNESP]; Herrera, Heitor Miraglia; Jesus Fernandes, Simone de [UNESP]; Sousa, Keyla Cartens Marques de [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Domingos, Iara Helena; Macedo, Gabriel Carvalho de; Machado, Rosangela Zacarias [UNESP] (Elsevier B. V., 2015)
Anaplasmataceae agents, piroplasmids and Hepatozoon spp. have emerged as important pathogens among domestic and wild felines. The present work aimed to detect the presence of species belonging to the Anaplasmataceae family, piroplasmas and Hepatozoon spp. DNA in blood samples of domesticated and stray cats in the city of Campo Grande, state of Mato Grosso do Sul, midwestern Brazil. Between January and April 2013, whole blood samples were collected from 151 cats (54 males, 95 females and two without gender registration) in the city of Campo Grande, state of Mato Grosso do Sul, Brazil. DNA extracted from cat blood samples was submitted to conventional PCR assays for Theileria/Babesia/Cytauxzoon spp. (18S rRNA, ITS-1), Ehrlichia spp. (16S rRNA, dsb, groESL), Anaplasma spp. (16S rRNA, groESL) and Hepatozoon spp. (18S rRNA) followed by phylogenetic reconstructions. Out of 151 sampled cats, 13 (8.5%) were positive for Ehrlichia spp. closely related to Ehrlichia canis, 1 (0.66%) for Hepatozoon spp. closely related to Hepatozoon americanum and Hepatozoon spp. isolate from a wild felid, 1 (0.66%) for Cytauxzoon sp. closely related do Cytauxzoon felis, and 18 (11.9%) for Babesia/Theileria (one sequence was closely related to Babesia bigemina, eight for Babesia vogeli, five to Theileria spp. from ruminants [Theileria ovis, Theileria lestoquardi] and four to Theileria sp. recently detected in a cat). The present study showed that Ehrlichia spp., piroplasmids (B. vogeli, Theileria spp. and Cytauxzoon spp.) and, more rarely, Hepatozoon spp. circulate among stray and domesticated cats in the city of Campo Grande, state of Mato Grosso do Sul, midwestern Brazil.
Keywords: Brazil; Cats; Ehrlichia spp.; Hepatozoon spp.; Piroplasmids